Formation of the 3' end of sea urchin U1 small nuclear RNA occurs independently of the conserved 3' box and on transcripts initiated from a histone promoter. - Wendelburg, B J (1992)
The formation of the 3' end of vertebrate small nuclear RNAs (snRNAs) requires that transcription initiate from an snRNA promoter. There is a loosely conserved required box 5 to 20 nucleotides (nt) 3' of the gene. The sea urchin snRNA genes contain promoter elements different from those of the vertebrate snRNAs. They also contain a characteristic 3' 15-nt sequence which is conserved among different sea urchin snRNA genes. We used microinjection of sea urchin U1 snRNA genes into sea urchin zygotes to define the sequence requirements for U1 snRNA 3'-end formation. Surprisingly, the conserved 3' box is not required for efficient 3'-end formation in vivo. Deletion analysis reveals that the 6 nt immediately 3' of the U1 snRNA are involved in 3'-end formation. Substitution analysis revealed that either these 6 nt 3' of the U1 RNA or the conserved 3' box could direct 3'-end formation. Transcripts initiated from a histone H4 promoter formed U1 3' ends about 50% as efficiently as transcripts initiated from the U1 promoter, even when the U1 end was placed in tandem with a histone 3'-processing signal, suggesting that transcription from an snRNA promoter is not necessary for formation of the 3' end of sea urchin U1 snRNA.